Military Spending, the Peace Dividend, and Fiscal Adjustment - Clements, Benedict; Davoodi, Hamid; Debaere, Peter; Schiff, Jerald (Washington, D.C. : International Monetary Fund, 1999)
The end of the Cold War has ushered in significant changes in worldwide military spending. This paper finds that the easing of (1) international tensions, (2) regional tensions, and (3) the existence of IMF-supported programs are related to lower military spending and a higher share of nonmilitary spending in total government outlays. These factors account for up to 66 percent, 26 percent, and 11 percent of the decline in military spending, respectively. Furthermore, fiscal adjustment has implied a larger cut in military spending of countries with IMF-supported programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet